(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to analyze the influence of sharia identity, female directors, and Return on Assets (ROA) on the value of companies in the automotive and component subsectors listed on the Indonesia Stock Exchange for the 2019–2023 period. The research uses a quantitative approach with the panel data regression method and the Random Effect model, as well as secondary data from the company’s financial statements. The results of the analysis showed that sharia identity and female directors had a negative but not significant effect on the company’s value, while ROA had a positive and significant effect. The determination coefficient (R²) of 29.88% showed that the independent variable was able to explain some of the variation in the company’s value, while the rest was influenced by other factors outside the research model. These findings provide empirical insights into the factors that affect the company’s value in the automotive and component subsectors, and emphasize the importance of a company’s financial performance in increasing the company’s market value.